2012
DOI: 10.1536/ihj.53.253
|View full text |Cite
|
Sign up to set email alerts
|

The Periodontal Pathogen Aggregatibacter Actinomycetemcomitans Deteriorates Ventricular Remodeling After Myocardial Infarction in Mice

Abstract: SummaryChronic inflammation plays a fundamental role in coronary heart disease (CHD). Periodontal disease is a common infectious disease and is a potential source of systemic inflammation. However, the effect of periodontal infection on CHD has not yet been proven. The purpose of this study was to determine the effect of periodontopathic bacteria on experimental myocardial infarction (MI). We implanted a chamber into the subcutaneous tissue of each male mouse. Aggregatibacter actinomycetemcomitans (A.a. n = 8)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…We measured the areas with a computer-assisted analyzer (Scion Image Beta 4.0.2). The fibrotic area ratio (fibrotic area/entire area expressed as a percentage) was calculated as described previously (20).…”
Section: Methodsmentioning
confidence: 99%
“…We measured the areas with a computer-assisted analyzer (Scion Image Beta 4.0.2). The fibrotic area ratio (fibrotic area/entire area expressed as a percentage) was calculated as described previously (20).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that 10% to 15% of the periodontal patients had been linked to CVD. [17][18][19] We previously showed that periodontopathic pathogens deteriorated ventricular remodeling after MI 20,21) and other cardiovascular diseases. [22][23][24][25][26] However, a detailed mechanism is still to be elucidated.…”
mentioning
confidence: 99%
“…5 Infection with P. gingivalis also accelerated neointimal formation after arterial injury in mice. 6 On the other hand, it was demonstrated that A. actinomycetemcomitans infection deteriorated ventricular remodeling after myocardial infarction 7 and pressure overload-induced myocardial hypertrophy. 8 These findings imply a hypothesis that a specific periodontal pathogen induces or promotes some particular cardiovascular diseases and that other pathogens influence different circulatory disorders.…”
mentioning
confidence: 99%